2021
DOI: 10.1007/s00259-021-05586-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in children and adolescents with differentiated thyroid carcinoma treated with total thyroidectomy and RAI: a real-life multicentric study

Abstract: Purpose This multicentric study aimed to investigate the main prognostic factors associated with treatment response at 1 year after radioactive iodine therapy (RAIT) and the last disease status in pediatric patients affected by differentiated thyroid carcinoma (DTC). Materials and methods In the period 1990–2020, all consecutive patients ≤ 18 years from six different centers were retrospectively included. Patients were classified as low, intermediate, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 30 publications
1
14
1
1
Order By: Relevance
“…In this cohort, pediatric DTC had a high incidence of LNM and distant metastasis (70.5% and 13.6%, respectively) as well as high rate of events (10 years EFS of 79.2%). This is consistent with several previous studies ( 8 , 12 , 22 25 ). Despite the presence of advanced disease in children with DTC in this cohort, long-term prognosis was excellent and 10 years overall survival was 98.4%, which is also in line with previous reports on pediatric DTC from different ethnicities ( 8 , 13 , 24 , 26 , 27 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this cohort, pediatric DTC had a high incidence of LNM and distant metastasis (70.5% and 13.6%, respectively) as well as high rate of events (10 years EFS of 79.2%). This is consistent with several previous studies ( 8 , 12 , 22 25 ). Despite the presence of advanced disease in children with DTC in this cohort, long-term prognosis was excellent and 10 years overall survival was 98.4%, which is also in line with previous reports on pediatric DTC from different ethnicities ( 8 , 13 , 24 , 26 , 27 ).…”
Section: Discussionsupporting
confidence: 94%
“…There are several reports where large tumor size and initial distant metastasis are found to have adverse impact on the recurrence and prognosis of pediatric DTC ( 14 , 24 , 28 , 29 ). Although several other factors have been previously reported to be negatively associated with EFS, such as age, extent of resection and serum thyroglobulin levels ( 8 , 25 , 30 ), in our study, age, ATA risk stratification and other clinico-pathological parameters (extrathyroidal extension, bilaterality, multifocality, lymphovascular invasion and response to therapy) were not independent risk factors for EFS.…”
Section: Discussioncontrasting
confidence: 82%
“…An analysis conducted by Al-Qahtani et al in children and adolescents with DTC under 18 years old has indicated that young age was dramatically related to the recurrence in situ ( 14 ). Domestic studies have compared specificity and difference in clinical characteristics of DTC between preadolescent children and adolescents; the incidence of distant metastases was reported to be higher in those of young age ( 16 ). This study first provides insights into the clinical features in DTC children younger than or equal to 13 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…However, the malignancy rate is 1/4, which is significantly higher than that in adults (2). The main bias of guidelines is the lack of detailed data and research, despite the particularity of the treatment and the fact that prognosis of pediatric differentiated TC patients have been clarified (14). Hence, further studies on pediatric TC remain to be investigated.…”
Section: Discussionmentioning
confidence: 99%